Does EFL Remote Learners' Anxiety Affect Their English Proficiency? A Case in A University Distant Classroom During Pandemic Covid-19 - Nur Habibah; Nurcahyo Nurcahyo; Rachmah Ganif Fiani; Irfan Cahyapradana (Edulitics (Education, Literature, and Linguistics) Journal, 2021)
Psychological traits like anxiety have long been linked to influencing test performance. Since the Covid-19 pandemic where tests are now conducted online, what students feel and experience may be different too. This study was born to investigate the students’ anxiety level during taking tests online, which anxiety type influences their online test-taking most, and how the overall correlation is. A total of 40 students in the second semester of the English Language Education Department in UIN Sunan Ampel Surabaya were asked via an online questionnaire. The result showed within 40 participants, only 6 of them were in an advanced level of English proficiency, around 452.15 on average, which had not exceeded 500 as the EFL university standards. While related to their test anxiety, anxiety management gave the most influence on their anxiety, and reading comprehension is the opposite. More importantly, related to the correlation of English proficiency and test anxiety, the result of this study showed the Pearson’s correlation coefficient between EFL learners’ anxiety and their English proficiency score is rs = -.144. It means the statistical analysis shows there was a correlation between EFL remote learners and their English proficiency test, although it was weak. It can be concluded that although students had a distant English proficiency test, the influence of their test anxiety was not really significant for weak correlation and only in a medium range.